English for nurse anesthetists in Indonesia: The needs analysis - Susandi, Ni Kadek Ary (JEES (Journal of English Educators Society), 2023)
ESP is a language teaching approach that targets the current and future academic or work needs of students, focusing on language, skills, discourse, and genres needed to meet the needs through specific teaching and learning methodologies (Anthony, 2015). Thus, the most prominent feature in the design of ESP course is the syllabus based on the students' needs analysis (Basturkmen, 2010). This study aimed to find out the needs of students and lecturers in the Diploma IV of Nursing Anesthesiology also nurse anesthetists in hospitals to design the ESP syllabus for students of Nursing Anesthesiology course in Indonesia. The needs analysis was conducted by distributing a set of questionnaires to all participants. The collected data were analyzed with descriptive statistics and further analyzed based on the comprehensive concept of needs analysis by (Dudley-Evans, T., & St John, 1998). The results revealed that the skills most needed in the target career are speaking and listening. In addition, all the twenty-four topics listed in the questionnaire were regarded as important, including some materials on cultural topics. Based on these findings, it is necessary to develop the ESP course for Indonesian nurse anesthetists with the integration of some cultural materials to help the students developing their communication skills to achieve effective cross-cultural communication in their current academic and future career as nurse anesthetists. English educators teaching this ESP course are recommended to have a fair knowledge about nurse anesthetist and anesthesia-related topics and implement a suitable teaching method emphasizing on teaching effective cross-cultural communication. HIGHLIGHTS: English was used significantly by the nurse anesthetists both in their academic and professional life, particularly spoken English. Along with speaking skills, a good listening skill is also vital, because effective communication between nurse anesthetist and patient requires not only the ability to speak but also to listen and comprehend the utterances spoken. Cultural topics and social skill merit to be included in the syllabus and exercised thoroughly in the learning activities to develop the learners’ communication skills to achieve interaction among cultures. Culturally competent nurse anesthetists will have the influence to improve the quality of anesthesia care leading to better health outcomes for culturally diverse patients.